Cerebral venous sinus thrombosis with concomitant subdural hemorrhage and subarachnoid hemorrhages involving cerebral convexity and perimesenchephalic regions: A case report. Issue 10 (8th October 2021) - Gajurel, Bikram Prasad; Shrestha, Ashish; Gautam, Niraj; Rajbhandari, Reema; Ojha, Rajeev; Karn, Ragesh
Abstract: We should suspect cerebral venous sinus thrombosis in patients with subacute onset progressive headaches with brain imaging evidence of localized cerebral edema with superimposed parenchymal, convexity subarachnoid as well as subdural hemorrhages. Abstract : We should suspect cerebral venous sinus thrombosis in patients with subacute onset progressive headaches with brain imaging evidence of localized cerebral edema with superimposed parenchymal, convexity subarachnoid as well as subdural hemorrhages.